Spatial scale of land‐use impacts on riverine drinking source water quality. Issue 3 (27th March 2013) - Hurley, Tim; Mazumder, Asit
Key Points Microbial water quality most closely related to local landuse Organic carbon concentrations only associated with entire watershed landuse Work supports watershed scale management to protect drinking water sources